Exploring the Prevalence and Dynamics of Domestic Gender-Based Violence in Mansehra City - Sheeraz Farooq; Ziaqat Farooq; Nizaqat Zaheer (Social Science Review Archives, 2025)
Domestic gender-based violence (DGBV) remains a critical and underreported social issue in Pakistan, particularly in semi-urban and rural areas like Mansehra City. This study aims to explore the prevalence, underlying causes, and socio-cultural dynamics contributing to DGBV within this specific context. Utilizing a mixed-methods approach, the research combines quantitative data collected through structured surveys with qualitative insights from in-depth interviews with survivors, local health workers, law enforcement officials, and community leaders. The study reveals a disturbingly high incidence of various forms of domestic violence—emotional, physical, economic, and sexual—predominantly affecting women across different age groups and socio-economic backgrounds. Key contributing factors identified include patriarchal norms, lack of education, economic dependency, weak legal enforcement, and social stigma surrounding the reporting of abuse. The findings also highlight the limited access to support services for victims, including legal aid, psychological counseling, and safe shelters. Cultural acceptance and normalization of violence further discourage victims from seeking justice. The study underscores the urgent need for targeted policy interventions, awareness campaigns, and community-based support mechanisms tailored to the socio-cultural realities of Mansehra. It concludes by recommending a multi-sectoral approach involving governmental and non-governmental stakeholders to address the root causes and provide sustainable support systems for affected individuals. This research contributes to the broader understanding of DGBV in Pakistan and serves as a foundation for future studies and policy formulations aimed at eradicating domestic violence at the grassroots level.